2021
DOI: 10.3390/molecules26206113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biologically Oriented Preparation Technique on the Stress Concentration of Endodontically Treated Upper Central Incisor Restored with Zirconia Crown: 3D-FEA

Abstract: The aim of this study was to evaluate the effect of biologically oriented preparation technique on the stress concentration of endodontically treated upper central incisors restored with zirconia crown (yttria-stabilized zirconia polycrystalline ceramic) through finite element analysis (FEA). Four models of maxillary central incisors containing enamel, dentin, periodontal ligament, cortical and medullary bone were created in CAD. Each model received a polymeric core-build up with nanofilled dental resin compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…A long-term follow-up indicated that abutment teeth mobility is one of the decisive prognostic factors for the success of RBFPDs ( Farshad et al, 2013 ). Furthermore, it was reported that an RBFPD without any retentive preparation design failed significantly at a higher rate ( Sichi et al, 2021 ). Saad et al suggested that the addition of retentive grooves made a statistically significant difference in resistance to debonding forces ( Saad et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…A long-term follow-up indicated that abutment teeth mobility is one of the decisive prognostic factors for the success of RBFPDs ( Farshad et al, 2013 ). Furthermore, it was reported that an RBFPD without any retentive preparation design failed significantly at a higher rate ( Sichi et al, 2021 ). Saad et al suggested that the addition of retentive grooves made a statistically significant difference in resistance to debonding forces ( Saad et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of vertical misfit has long been recognized as a significant concern in implant dentistry. Vertical misfit refers to the discrepancy between the implant fixture and the abutment, which can lead to complications such as peri-implant bone loss, implant failure, and compromised esthetics [ 33 , 34 , 35 ]. The prosthetic–abutment vertical misfit in clinical settings usually ranges from 50 to 160 μm in implant-supported prostheses manufactured using the casting technique [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean fracture loads for the VP (1432 + 809 N) although it was less than HP, it still exceeded the maximum chewing forces reported in the literature in the posterior region (300 -850 N) [23]. Accordingly, this means that vertical preparation design could be an alternative to the less conservative chamfer and shoulder margin designs and can be used in certain clinical situations, such as severely damaged teeth, endodontically treated teeth, periodontally affected teeth and implant supported restorations where margin needs to be placed deep subgingival following the BOPT concept [24,25]. O u r r e s u l t s a g r e e d w i t h s e v e r a l studies [19,[26][27][28], which reported that a 1 mm deep shoulder finishing line with a rounded internal line angle has better fracture strength for all ceramic crowns and provide more even stress distribution than other preparation design.…”
Section: Nouh I Et Almentioning
confidence: 95%